ASSOCIATION OF EMOTIONAL INTELLIGENCE WITH ACADEMIC PERFORMANCE AMONG MEDICAL STUDENTS IN SOUTH INDIA - Unnikrishnan, Bhaskaran; Bb, Darshan; Kulkarni, Vaman; Thapar, Rekha; Mithra, Prasanna; Kumar, Nithin; Holla, Ramesh; Kumar, Avinash; Sriram, Rithika; Nair, Namitha; et al. (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: The present study was designed to assess the association of emotional intelligence (EI) with academic performance among medical students. Methods: A self-administered semi-structured questionnaire was used to collect the information. Schutte self-report EI test was used for the study and the items were scored from 1 (strongly disagree) to 5 (strongly agree) based on 5-point Likert scale. Data were analyzed using SPSS version 11.5. The scores of EI obtained were then categorized into low (33-77), moderate (78-121) and high (122-165). The results obtained were then expressed as proportions, statistical test Chi-square was used and p<0.05 was considered statistically significant. Results: A total of 532 participants were assessed for EI. Around 1.9% had low EI, 61.8% had moderate EI and 36.3% had high EI. Gender, academic performance and satisfaction with the career choice were found to be statistically significant with EI. Conclusion: Significant association was found between that of EI and academic performance and efforts must be made to include the concept of EI into the medical curriculum. Keywords: Emotional intelligence, Medical students, South India.